(untitled) (Tamaddun, 2022)
Immanuel Kant, the eminent Western philosopher, discusses several significant themes in the context of political ideas that are strewn across his various books. In this study, one of the challenges is to organise Kant’s valuable notes on political ideas in a systematic yet critical manner to reflect his philosophy of law. Kant’s theoretical and practical philosophies have influenced the idea of law, which is an a priori concept of the human mind, in several ways. It is also conceivable, by virtue of Kant’s philosophy of law, to identify the inherent connection between moral and political philosophy. This study will illustrate the connection between the moral and political philosophy of Immanuel Kant and the philosophy of law. This work is carried out through the method of context and critical analysis. This work is organised into three sections. The first portion of the introduction will analyse the definition of law and its connection to the philosophy of law; the second part will study the broad notion of law and its different varieties; and the third section will investigate whether Kant’s political philosophy is consistent enough to accommodate the different types of laws. This work submits that Kant’s philosophy is quite consistent with the philosophy of law. In particular, this work submits that there is a theoretical link between Kant’s political philosophy and natural law, moral law, political law, international law, and cosmopolitan law.